PENGARUH FASE BULAN TERHADAP HASIL TANGKAPAN GLASS EEL DI MUARA SUNGAI CIBUNI TEUGAL BULEUD, KABUPATEN SUKABUMI - Suhendar, Dadan; Wahju, Ronny I; Soeboer, Deni Achmad (Jurnal Teknologi Perikanan dan Kelautan, 2017)
Cibuni River estuary , Tegal Buleud , Sukabumi the waters of the south coast of Java Island which has great potential in the supply of glass eel but have not done the research as well as in the mouth of the River Cimandiri Pelabuhanratu . Catching eels seeds done at night when the tide thus the phase of the moon will affect the fishing operation , therefore, this study aims to determine the age of moon phases to catch glass eel. Data collected from daily data glass eels catches of fishermen collecting for 12 months in 2015 and then the data were analyzed using a completely randomized design (CRD) by classifying into 4 phases of the moon (medium bright , bright moon , medium dark and dark moon) . From the results of analysis show that catches the light in different phases of the real against the dark phase of the moon with everage catches glass eel in light phase 6.2 kg and dark phase 18.3 kg and catches of phases the moon the medium bright differ significantly on phases of the moon light of the while catches in the phase of medium bright with the dark moon no significant difference.